Chromosome-level genome assembly of Monolepta hieroglyphica, two-spotted leaf beetle (Coleoptera: Chrysomelidae) - Hao He; Yongxin Zhao; Dengyu Zheng; Huiyun Kuang; Fei Shen; Kang He; Haiyan Zhang; Changjiang Zhao; Lu Jiang; Da Xiao; Su Wang; Zhenying Wang; et al. (Scientific Data, 2025)
Abstract Monolepta hieroglyphica, in view of its wide-ranging host and highly polyphagous characteristics, has become an important agricultural pest in East and Southeast Asian countries. To better understand its biology and develop control strategies, we present a high-quality chromosome-level genome assembly of M. hieroglyphica, with contig N50 of 18.62 Mb and scaffold N50 of 241.916 Mb. Using 156x Hi-C data, we anchored a total length of 2,313 Mb (91.9% of the genome) to nine chromosomes. We predicted 46,561 genes using an integrated approach. The completeness of the final reported genome and proteome were assessed by BUSCO and show high values of 99.4% and 95.2%, respectively. The high-quality chromosome-level genome assembly of M. hieroglyphica will be a useful molecular resource for the communities of both beetle and crop protection.